Tax knowledge and compliance behavior under Self-Assessment System(SAS): perception of students from higher education in Malaysia - Liew, Wei Lee; Isa, Khadijah; Yussof, Salwa Hana (2017)
Tax non-compliance is a subject that has attracted substantial discussion not only within policy circles but also within the academia. The non-compliance issue is very important as the compliance rate will affect the revenue collection from taxpayers of a country. In view of the importance of tax compliance behavior, the present study aims at (1) examining the level of tax knowledge, attitudes and subjective norms, and intention towards tax compliance, (2) comparing the level of tax knowledge and the intention towards tax compliance between those with tax knowledge via formal tax education and those without formal tax education, and (3) investigating factors influencing tax compliance intention based on Theory of Reasoned Action. The study adopts a survey methodology and gathers a sample of diploma and undergraduate students from fourteen higher institutions of learning in Malaysia, a total of 417 were received and usable (92% response rate). In order to achieve the research objective, T-test, Pearson’s correlation analysis and multiple regression analysis were performed. The findings suggest that the level of tax knowledge among the students is moderate and those who have been exposed to formal tax education possess more tax knowledge. Similarly, those who have been exposed to formal tax education have higher intention towards tax compliance. The findings further reveal that tax knowledge, attitudes and subjective norms are significantly and positively correlated with intention toward tax compliance. It is further noted that, while tax knowledge is positively correlated with intention towards tax compliance, it lacks significance once the roles of attitudes and subjective norms are analysed in the multiple regression setting. Perhaps, tax knowledge plays an indirect role in shaping attitudes of the future taxpayers towards tax compliance intention. Instead, attitudes and subjective norms are found to be most influential and to have predictive ability for intention toward tax compliance. The result of the current study may contribute to policy makers, academics and tax administrators especially in developing tax education programmes to increase the awareness and tax knowledge among students (future taxpayers) and consequently, to enhance tax compliance rate and to reduce compliance cost.